Gestational trophoblastic neoplasia: management and outcomes with EMACO regimen - Gupta, Nidhi; Kaur, Paramdeep; Dimri, Kislay; Arora, Aanchal; Kaur Pandher, Dilpreet; Takkar, Navneet; Pandey, Awadhesh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Gestational trophoblastic neoplasia (GTN) is a rare and malignant condition arising from the maternal placental tissue. It is a highly chemo sensitive tumor, EMACO (etoposide/methotrexate/dactinomycin alternating with cyclophosphamide and vincristine) is the most common multiagent chemotherapy used for patients with high risk. An audit was conducted for patients with gestational trophoblastic disease (GTN) receiving EMACO regimen during the past five years at a tertiary care referral centre. Records were analysed for efficacy, toxicity and outcomes with EMACO regimen. Total of eight patients received EMACO during the study period. Median age at presentation was 25 years. All patients, except one gave a history of an antecedental molar pregnancy. The mean duration of development of GTN from the index pregnancy was 3.4 months. FIGO stage I, II and III were seen in one, three and four patients respectively. The average quantitative human chorionic gonadotrophin (hCG) prior to starting EMACO was 157,705 IU/L (6149-629,442 IU/L). The mean number of EMACO cycles for achieving normal hCG levels was 4 (2-6). All but one patient also received two additional cycles of consolidation chemotherapy. Grade 3/4 neutropenia was seen in seven patients. Hepatotoxicity was seen in one patient. At a median follow up of 36 months (18-50 months), all but one patient was alive, and four patients have successfully conceived, while three delivered healthy babies after receiving EMACO regimen. EMACO is a highly effective regimen with manageable toxicity, good patient compliance and fertility preservation. EMACO administration requires experienced multidisciplinary team approach which can help to adequately monitor response, manage toxicity, provide supportive care and detect early relapses.